Treatment of Bloodstream Infections Due to Gram-Negative Bacteria with Difficult-to-Treat Resistance - Matteo Bassetti; Antonio Vena; Chiara Sepulcri; Daniele Roberto Giacobbe; Maddalena Peghin (MDPI AG, 2020)
The rising incidence of bloodstream infections (BSI) due to Gram-negative bacteria (GNB) with difficult-to-treat resistance (DTR) has been recognized as a global emergency. The aim of this review is to provide a comprehensive assessment of the mechanisms of antibiotic resistance, epidemiology and treatment options for BSI caused by GNB with DTR, namely extended-spectrum Beta-lactamase-producing Enterobacteriales; carbapenem-resistant Enterobacteriales; DTR Pseudomonas aeruginosa; and DTR Acinetobacter baumannii.